1989
DOI: 10.1007/bf02365897
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in using shorebird counts for assessing long-term changes in wader numbers in the Wadden Sea

Abstract: Over the past 20 years, a tradition has developed in western Europe of carrying out shorebird surveys in estuaries. These counts are mostly conducted by amateur ornithologists, usually well acquainted with the area in which they are active. The results of these surveys are well reproducible for at least the abundant species, and information is available on the size of the errors which occur. In several parts of Europe, shorebird surveys have been carried out long enough to allow trend analysis of population si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…At the same time, aircraft disturbance is difficult to study since performing experiments is hardly feasible (but see Ward et al, 1999), and most studies rely on observations at sites where aircraft overflights are common (Blackwell et al, 2019;van der Kolk, Krijgsveld, et al, 2020). Many studies highlighted large differences in disturbance potential among aircraft types (Blackwell et al, 2019;Goudie, 2006;Komenda-Zehnder & Bruderer, 2002;Smit & Visser, 1993;van der Kolk, Krijgsveld, et al, 2020), but sometimes with contrasting rankings. For example, Komenda-Zehnder and Bruderer (2002) concluded that transport aircraft were less disturbing than jets, helicopters and small civil airplanes, whereas van der Kolk, Krijgsveld, et al (2020) showed that transport aircraft had by far the highest disturbance potential among these same types of aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, aircraft disturbance is difficult to study since performing experiments is hardly feasible (but see Ward et al, 1999), and most studies rely on observations at sites where aircraft overflights are common (Blackwell et al, 2019;van der Kolk, Krijgsveld, et al, 2020). Many studies highlighted large differences in disturbance potential among aircraft types (Blackwell et al, 2019;Goudie, 2006;Komenda-Zehnder & Bruderer, 2002;Smit & Visser, 1993;van der Kolk, Krijgsveld, et al, 2020), but sometimes with contrasting rankings. For example, Komenda-Zehnder and Bruderer (2002) concluded that transport aircraft were less disturbing than jets, helicopters and small civil airplanes, whereas van der Kolk, Krijgsveld, et al (2020) showed that transport aircraft had by far the highest disturbance potential among these same types of aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the concordance between aerial observations and the actual number of breeding birds (i.e., the detection rate) has not been established for boreal-nesting shorebirds, or for most small birds. With no objective measurement of bias, the reliability of aerial surveys for shorebirds is unknown (Smit 1989). In this study, we attempted to measure detection rates for aerial surveys of three species of boreal-nesting shorebirds, and examined what parameters affected detection.…”
mentioning
confidence: 99%